World forum on smart materials and smart structures technology : proceedings of the World Forum on Smart Materials and Smart Structures Technology (SMSST '07), Chongqing & Nanjing, China, 22-27 May, 2007 /: proceedings of the World Forum on Smart Materials and Smart Structures Technology (SMSST '07), Chongqing & Nanjing, China, 22-27 May, 2007. (©2008) - Unknown
No abstract available